Effects of Oxygen on Exercise Duration in Chronic Obstructive Pulmonary Disease Patients before and after Pulmonary Rehabilitation - Nha Voduc; Caroline Tessier; Elham Sabri; Dean Fergusson; Lyne Lavallee; Shawn D Aaron (Canadian Respiratory Journal)
BACKGROUND: Supplemental oxygen therapy has been shown to improve exercise performance in patients with chronic obstructive pulmonary disease (COPD). It is unknown whether the magnitude of this benefit would be affected by participation in a pulmonary rehabilitation program.